Syntheses of 1,3-bis(2-arylimino)isondoline type ligands and some metal complexes containing EDOT moiety - Goktug, Ozge; Korkut, Sibel Eken; Gokce, Busra Nur; Tekbasoglu, Tugce Yazici; Sener, Kasim (SAGE PUBLICATIONS INC, 2018)
EDOT (3,4-ethylenedioxythiophene) substituted 1,3-bis(2-arylimino)isoindoline derivatives EDOT-BAI1, EDOT-BAI2, EDOT-BAI3, and EDOT-BAI4 have been synthesized according to the Linstead or Siegl's method. Preparation of palladium(II) and platinum(II) complexes of EDOT-BAI1 and EDOT-BAI2 have been also accomplished in this study. The new compounds have been characterized by FT-IR, NMR, UV-Vis spectroscopies and via mass spectrometric analysis. The present EDOT derivatives provide new starting materials that may be useful in the synthesis of new, functional electropolymers.
Keywords: Poly(3,4-ethylenedioxythiophene); bis(arylimino)isoindoline; platinum; palladium; CONDUCTING POLYMERS; ELECTROPOLYMERIZATION; ISOINDOLINE; COPOLYMER; GLUCOSE; Chemistry